Chemosensitivity of IDH1-mutated gliomas due to an impairment in PARP1-mediated DNA repair - Lu, Yanxin (Cancer Res, 2017)
Mutations in isocitrate dehydrogenase (IDH) are the most prevalent genetic abnormalities in lower grade gliomas. The presence of these mutations in glioma is prognostic for better clinical outcomes with longer patient survival. In the present study, we found that defects in oxidative metabolism and 2-HG production confer chemosensitization in IDH1-mutated glioma cells. In addition, temozolomide (TMZ) treatment induced greater DNA damage and apoptotic changes in mutant glioma cells. The PARP1-associated DNA repair pathway was extensively compromised in mutant cells due to decreased NAD+ availability. Targeting the PARP DNA repair pathway extensively sensitized IDH1-mutated glioma cells to TMZ. Our findings demonstrate a novel molecular mechanism that defines chemosensitivity in IDH-mutated gliomas. Targeting PARP-associated DNA repair may represent a novel therapeutic strategy for gliomas.